Gas6 as a putative noninvasive biomarker of hepatic fibrosis. (December 2016) - Bellan, Mattia; Pogliani, Gabriele; Marconi, Cecilia; Minisini, Rosalba; Franzosi, Lisa; Alciato, Federica; Magri, Andrea; Avanzi, Gian Carlo; Pirisi, Mario; Sainaghi, Pier Paolo
Aim: To evaluate serum growth arrest-specific gene 6 (Gas6) concentration as a biomarker of liver fibrosis progression.Materials & methods: One hundred and thirteen consecutive patients affected by chronic liver disease underwent transient elastography, Gas6 measurement and, if clinically indicated, liver biopsy.Results: Gas6 concentration was directly correlated to liver stiffness (r = 0.67; p < 0.0001) and was significantly higher in patients with advanced fibrosis (Ishak 4–5; p < 0.001). A plasma concentration <30 ng/ml Gas6 ruled out fibrosis with 84% sensitivity and 56% specificity, while values >42 ng/ml identified severe fibrosis with a sensitivity of 64% and a specificity of 95%; the diagnostic accuracy was comparable to that of transient elastography.Conclusion: Gas6 is a novel biomarker of liver fibrosis, with a potential clinical and pathophysiological relevance.